Inequality in Post Earthquake Reconstruction: An Ethnographic Account of a Peri-urban Locality in the Northern Part of Kathmandu - Aryal, Kumar Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Scholars have carried out studies on different dimensions of the 2015 earthquakes. However, inequality in reconstruction has not been understood sufficiently in the context of Nepal. Taking this issue into consideration, this paper explores the issues of inequality in the reconstruction of private houses of different classes and caste/ethnic groups during the recovery from the earthquake. Based on this context study focuses on the behavioral and organizational response approach to disaster to handle the reconstruction process. This research was conducted in Dharmasthali of Kathmandu district in April 2016. The study adopted an ethnographic approach based on both primary and secondary sources. Data was collected through participant observation, in-depth interviews, key informant interviews, and informal discussions with earthquake victims, and representatives of government officials and different community-based organizations. Immediately after the earthquake, victims built temporary shelters either on their own or with support from state and non-state actors. The temporary shelters built by the people revealed the unequal capacity of the victims for reconstruction and also existing social inequality. The study shows that the poorer sections of the community bear the significant impact of disasters like earthquakes. Those with access to resources can construct their homes easily, but the poor face significant challenges in reconstruction. The study concludes that during disasters there is a need for government assistance to be generous and rules to be sufficiently flexible to enable the poorer victims to reconstruct their homes and lives.